2019
DOI: 10.2478/tjeb-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of International Remittance Inflows on Nigeria’s Trade Balance

Abstract: While international remittance inflow is globally recognized as a key source of income for improved standard of living and poverty reduction, there is an ongoing intellectual debate that persistent remittance inflow causes deterioration in trade balances, by inducing import-led consumption expenditures, especially in developing countries like Nigeria. The study investigated the impact of international remittance inflows on Nigeria’s trade balances from 1990 to 2016. The study uses the contemporary econometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…On the empirical side, Şen et al (2018) studied the causality between expenditure on education, expenditure on health and economic growth for selected developing countries over the period 1995-2012 and found mixed results for different sets of countries. Similarly, a study by Maduka et al (2016) reported that the government health expenditures in Nigeria indirectly affect its economic growth by influencing health outcomes, such as the mortality and life expectancy rates. However, Gupta and Mitra (2004) found that per capita public health expenditure positively leads to a decline in poverty and improves growth in 15 states of India.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…On the empirical side, Şen et al (2018) studied the causality between expenditure on education, expenditure on health and economic growth for selected developing countries over the period 1995-2012 and found mixed results for different sets of countries. Similarly, a study by Maduka et al (2016) reported that the government health expenditures in Nigeria indirectly affect its economic growth by influencing health outcomes, such as the mortality and life expectancy rates. However, Gupta and Mitra (2004) found that per capita public health expenditure positively leads to a decline in poverty and improves growth in 15 states of India.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Conventional wisdom suggests that health is vital to the well-being of humanity as a whole, as well as a condition for increased productivity and overall economic growth and economic development (Maduka et al, 2016). For more than half a century, the issue of how countries should improve economic growth has been a contentious and much disputed topic in the context of development economics, no matter how developed countries are.…”
Section: Introductionmentioning
confidence: 99%
“…Public health expenditures can differ significantly between countries depending on variables including population size, disease prevalence and economic development. This suggests that public health expenditure is an important indicator of a government's commitment to promoting the health and well-being of its citizens (Maduka, Madichie, & Ekesiobi, 2016). Adequate public health expenditure is essential for ensuring access to quality healthcare services and for addressing public health challenges such as infectious diseases, non-communicable diseases and environmental health hazards.…”
Section: Public Health Expenditurementioning
confidence: 99%
“…After oil trade receipts, remittance inflow ranks as Nigeria's top foreign capital inflow source and second-highest foreign exchange source (Ude et al, 2018;Maduka et al, 2019;Nwokoye et al, 2020). While external portfolio and FDI totalled US$12.2 billion in the country (NBS, 2018;World Bank, 2018), Nigeria received about US$22 billion in remittances in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike similar existing studies (Birdsall and Wheeler,1993;Taylor, 2005;Ederington and McCalman, 2009;Baghebo and Apere, 2014;Mert and Bölük, 2016;Huang et al, 2019;Rahman, 2019;Adams and Opoku, 2020;Essandoh et al, 2020;Gill et al, 2020;Mahadevan and Sun, 2020;Halliru et al, 2021) that included either remittances or regulatory quality in their estimations, as well as those that ignore both, this study represents a novel effort to incorporate both variables in our model testing the PHH within the EKC framework. For many developing countries, remittances remain the secondlargest source of foreign financial support behind FDI, but for some, they account for the majority of capital inflows, outpacing export earnings, FDI, and foreign aid (Meyer and Shera, 2016;Maduka et al, 2019;Ekesiobi et al, 2016). Remittances enhance GDP per capita, thus increasing energy demand and impacting the environment in poorer nations (Rahman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%